Two new genera of pyroglyphid mites, Tuccioglyphus and Marioglyphus, with a key to genera of the World (Acari: Pyroglyphidae) - Horn, Tamara Bianca; Ferla, Júlia Jantsch; Körbes, Júlia Horn; Körbes, Júlia Horn; Granich, Juliana; Oconnor, Barry; Klimov, Pavel; Ferla, Noeli Juarez (Zootaxa, 2017)
We describe Tuccioglyphus setosus gen. et sp. nov. from the litter of commercially reared laying hens as well as wild birds in Brazil. The new genus Tuccioglyphus presents a mixture of character states between the two conventional subfamilies, Pyroglyphinae and Dermatophagoidinae. Based on this new unusual genus, we discuss character states delimiting these and other major subfamilies of the house dust mite family, Pyroglyphidae, as well as its most important and species-rich genus Dermatophagoides. An additional new genus, Marioglyphus gen. n., is proposed for Hughesiella valerioi Vargas and Smiley. Both Tuccioglyphus and Marioglyphus are related to the genus Hughesiella. A key to pyroglyphid genera of the World is presented.